Effect of Plasticizers on the Physicochemical Properties of Bioplastic Extracted from Banana Peels - Chapain, Khagendra; Shah, Sambridhi; Shrestha, Binod; Joshi, Rajendra; Raut, Naresh; Pandit, Rajesh (Journal of Institute of Science and Technology, 2021)
Plasticizers are the binding substances used to increase the elasticity of materials. In this research work, bioplastic is extracted from banana peels using various plasticizers such as, glycerol, urea, distilled water and glucose. The prepared bioplastics were characterized by using Fourier-transform infrared spectroscopy (FTIR) spectroscopic analysis which showed that the peak at 3355 cm-1 indicate the H-bonding formation between N-H urea and starch. The physicochemical properties such as water absorption test, soil decomposition and load test of synthesized bioplastics were analyzed at ambient temperature. The water uptake analysis showed that bioplastic absorbs water for up to 4 days without being decay. The load test showed that urea plasticized bioplastic has a high tensile strength of 2.3 KPa. The result revealed that the bioplastic with glucose as a plasticizer showed the effective result in water uptake and soil decomposition test whereas the urea plasticized bioplastic showed relatively good tensile strength.